Transformation of financial planning and management processes at enterprises as a response to economic challenges - Khatser, Maxim (Management and Entrepreneurship: Trends of Development, 2023)
The article is devoted to forming new scientific solutions regarding the search for ways to transform the planning processes and financial management at Ukrainian enterprises as a response to economic challenges in the country. It has been proven that Ukrainian enterprises need to transform the planning processes and financial management and make changes to the system elements of planning and management activities (goals, tasks, subjects, objects, the subject, conditions, principles, and methods). The article aims to reveal directions of transformation of planning and financial management processes at Ukrainian enterprises as a response to economic challenges in the country. Methodology: a complex of general and special methods has been used at the empirical and theoretical levels, such as the method of abstraction to determine the system elements of planning and management activities of Ukrainian enterprises that need transformation; the method of literary analysis for the study of scientific developments in the field of planning and financial management at enterprises; a comparison method for detailing the transformation of system elements of planning and management activities of Ukrainian enterprises; methods of systematization, grouping, and logical generalization for systematization of information, formation of conclusions and scientific proposals of the article. The article has used systemic and functional, historical and systemic approaches in revealing and solving the problem of finding directions for the transformation of planning and financial management processes at Ukrainian enterprises as a response to economic challenges in the country. Results: it has been identified and proposed to use directions for the transformation of the planning processes and financial management at Ukrainian enterprises as a reaction to economic challenges in the country, emphasizing making changes to the system elements of planning and management activities (purpose, tasks, subjects, objects, the subject, conditions, principles, and methods). JEL Classification: D 21, М 11, M21